Q-sort as a tool for promoting outstanding leadership. Issue 1 (2nd January 2022) - Howard, Colin; Dhillon, Jaswinder K
ABSTRACT: The need for outstanding leadership in education and professional practice has been brought into sharper focus during the COVID-19 pandemic. Crises, such as this global pandemic, often place additional burdens on leaders and other professionals who are seeking to achieve high-quality education for all pupils. We offer a tool for leaders and managers to use with their teams to develop outstanding leadership in their organisations. The tool, a Q-sort on characteristics of outstanding leadership, has been developed using Q-methodology with leadership teams working in primary, secondary and post-compulsory education. This article outlines strategies for using the Q-sort to promote discussion and reflection in relation to participants' own experiences of leadership, management and governance in different contexts. Our participants found that discussion around the characteristics of outstanding leadership was a non-threatening process for developing their own leadership practice and guiding them in future actions.